Assessment Practices in the Digital Age: A Comprehensive Review - Rajeshwari Garg (AG Volumes, 2024)
The National Education Policy (NEP) 2020 in the country brings about a number of paradigm shifts within the educational system, with a specific focus on assessment methodologies. The objective of these modifications is to transition from conventional learning methods that emphasise exams to assessments that are more comprehensive, competency-driven, and ongoing. The following paper provides an analysis of digital learning and its transition from traditional approaches to a digital era via diverse assessment methodologies.